2020
DOI: 10.1111/tbj.13491
|View full text |Cite
|
Sign up to set email alerts
|

Changing practice patterns of adjuvant radiation among elderly women with early stage breast cancer in the United States from 2004 to 2014

Abstract: Randomized controlled trials (RCTs) have challenged the need for routine radiation therapy (RT) in women ≥ age 70 with favorable early stage breast cancer (BC) due to modest improvement in local control and no survival benefit. We studied practice patterns in RT among elderly women in the United States. We analyzed data from the National Cancer Database (NCDB) of women ≥age 70 diagnosed with T1 or T2 and N0 invasive BC treated with breast conservation surgery (BCS) between 2004 and 2014. Patients were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Therefore, competing mortality is a major factor affecting survival in elderly BC patients. However, several studies have shown that comorbidities, education level, area of residence, receipt of endocrine therapy, and distance to the nearest RT clinic were not associated with the omission of RT after BCS in this population ( 14 , 19 ). In clinical practice, age, marital status, and tumor grade were the main factors associated with RT decision-making in the elderly ( 14 , 19 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, competing mortality is a major factor affecting survival in elderly BC patients. However, several studies have shown that comorbidities, education level, area of residence, receipt of endocrine therapy, and distance to the nearest RT clinic were not associated with the omission of RT after BCS in this population ( 14 , 19 ). In clinical practice, age, marital status, and tumor grade were the main factors associated with RT decision-making in the elderly ( 14 , 19 ).…”
Section: Discussionmentioning
confidence: 89%
“…However, several studies have shown that comorbidities, education level, area of residence, receipt of endocrine therapy, and distance to the nearest RT clinic were not associated with the omission of RT after BCS in this population ( 14 , 19 ). In clinical practice, age, marital status, and tumor grade were the main factors associated with RT decision-making in the elderly ( 14 , 19 ). In our study, we also found that patients with younger age and higher tumor grade were more likely to receive RT.…”
Section: Discussionmentioning
confidence: 89%
“…According to the latter, radiation omission is not an option after BCS, and IORT has been very recently recommended (after this survey was performed) for highly selected patients [ 13 ]. In our study, there is no consensual agreement between physicians for IORT, and none of them were willing to propose radiation omission even in the context of clinical trial and knowing that it was considered a therapeutic option in several countries [ 9 ]. Of note, even in countries that recommend radiation omission as a de-escalation option, there is no consensus among radiation oncologists and surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-structured interviews were conducted with open-ended questions on IORT, de-escalation, and patients’ information needed to participate in such decision making. Radiotherapy omission was also systematically discussed as proposed in several countries [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation